The impact of wood fuel energy on economic growth in sub-Saharan Africa: dynamic macro-panel approach - Sulaiman, Chindo; Abdul Samad @ Iammi, Abdul Rahim (MDPI, 2020)
This study estimates the impact of wood fuel consumption on economic growth in 19 sub-Saharan African countries over the 1979-2017 period. The study employs dynamic macro-panel estimators, which comprises pooled mean group (PMG), mean group (MG), and dynamic fixed effects (DFE). The estimated result reveals that PMG is the most efficient estimator among the three estimators based on the Hausman h-test. The results from PMG model reveal that wood fuel consumption has significant negative impact on economic growth. Also, when an interaction term between labor and wood fuel consumption was included in the model and estimated, the coefficient of wood fuel consumption yields negative and significant coefficient. This suggests that the interaction term has a negative and significant effect on economic growth. These results unveil that wood fuel consumption negatively and significantly affect economic growth, both directly and indirectly. The policy recommendations from this study are as follows: (1) Governments of these countries should provide adequate and affordable modern fuels to the populace; especially rural dwellers to decrease the use of wood fuel for cooking and heating (2) policy makers should intensify awareness campaign on the risk and danger wood fuel poses to economic growth so as to discourage its use and (3) policy makers should provide adequate solar powered stoves and solar-powered room heaters as cheap substitutes to the use of wood fuel for cooking and heating. These recommendations will assist in negating the negative effects of wood fuel consumption on economic growth of the region.